Antiobesity and emetic effects of a short-length peptide YY analog and its PEGylated and alkylated derivatives. Issue 3 (1st February 2018) - Niida, Ayumu; Kanematsu-Yamaki, Yoko; Asakawa, Tomoko; Ishimura, Yoshimasa; Fujita, Hisashi; Matsumiya, Kouta; Nishizawa, Naoki; Adachi, Yusuke; Mochida, Taisuke; Tsuchimori, Kazue; Yoneyama-Hirozane, Mariko; Sakamoto, Junichi; et al.
Graphical abstract: Abstract: Neuropeptide Y2 receptor (Y2R) agonism is an important anorectic signal and a target of antiobesity drug discovery. Recently, we synthesized a short-length Y2R agonist, PYY-1119 (4-imidazolecarbonyl-[d -Hyp 24, Iva 25, Pya(4) 26, Cha 27, 36, γMeLeu 28, Lys 30, Aib 31 ]PYY(23–36), 1 ) as an antiobesity drug candidate. Compound 1 induced marked body weight loss in diet-induced obese (DIO) mice; however, 1 also induced severe vomiting in dogs at a lower dose than the minimum effective dose administered to DIO mice. The rapid absorption of 1 after subcutaneous administration caused the severe vomiting. Polyethylene glycol (PEG)- and alkyl-modified derivatives of 1 were synthesized to develop Y2R agonists with improved pharmacokinetic profiles, i.e., lower maximum plasma concentration (Cmax ) and longer time at maximum concentration (Tmax ). Compounds 5 and 10, modified with 20 kDa PEG at the N-terminus and eicosanedioic acid at the Lys 30 side chain of 1, respectively, showed high Y2R binding affinity and induced significant body weight reduction upon once-daily administration to DIO mice. Compounds 5 and 10, with their relatively low Cmax and long Tmax, partially attenuated emesis in dogs compared with 1 . These results indicate that optimization of pharmacokinetic properties of Y2R agonists is an effective strategy to alleviate emesis induced by Y2R agonism.